PROSPECTS AND CHALLENGES OF UKRAINIAN EUROPEAN INTEGRATION - Скрипник, Олена (Modern engineering and innovative technologies, 2023)
The paper examines Ukraine’s European integration path and its future prospects, achievements and failures in the European integration policy, possible positive and negative consequences for Ukraine from joining the European Union. Achievements and failur